Prevention of pressure sores by identifying patients at risk. Issue 6326 (8th May 1982) - Andersen, K E; Jensen, O; Kvorning, S A; Bach, E
Abstract : The risk of pressure sores developing in patients admitted with acute conditions was assessed by a simple risk score system based on age, reduced mobility, incontinence, pronounced emaciation, redness over bony prominences, unconsciousness, dehydration, and paralysis in a prospective clinical study. During seven months in 1977, 600 of 3571 patients were classified as at risk. Of these 35 (5.8%) developed sores compared with five (0.2%) of those not at risk. The results of this study compared with those over the same period in 1976 show that close observation of at-risk patients and early detection of pressure sores prevents their development.